Battery degradation minimization oriented energy management strategy for plug-in hybrid electric bus with multi-energy storage system. (15th December 2018) - Du, Jiuyu; Zhang, Xiaobin; Wang, Tianze; Song, Ziyou; Yang, Xueqing; Wang, Hewu; Ouyang, Minggao; Wu, Xiaogang
Abstract: The potential of reducing fuel consumption, harmful emission and cost benefit for plug-in electric hybrid buses depended largely on the power management strategy for specific hybrid electric powertrain configuration, especially for those with compound energy storage system. Hybrid energy storage system in this research comprise high energy lithium iron phosphate batteries and super-capacitors, therefore, the key of improving the life cycle cost-benefit is to extend the cycle life for lithium battery. This paper presents an optimal control strategy for the serial-parallel plug-in hybrid electric buses based on the lithium battery degradation model to minimize life cycle operating cost. To derive the globally optimal strategy, an algorithm based on two-dimensional Pontryagin's minimum principle is proposed. With the optimal strategy, the battery degradation is significantly reduced, and the total cost is reduced by 21.7% compared with a plug-in hybrid electric bus with single type energy storage. Further embodies the advantages of hybrid energy storage systems and optimization algorithms. Highlights: The plug-in hybrid electric bus powertrain with HESS consist of lithium battery and super-capacitor. A dynamic simulation model of battery capacity degradation for HESS is established. A 2-dimension PMP algorithm is proposed for HESS power management strategy. The proposed optimal strategy of HESS reduces battery degradation significantly. The lithium battery degradation and life-cycle cost are simultaneously minimized.